Prisão e liberdade no processo penal militar - Valle, Dirceu Augusto da Câmara (2009)
The dissertation aims to the proposed work, and discuss matters little face and that even the doctrine is discussed throughout the course of studies, demonstrate the need for adequacy of criminal procedural law the Military Federal Constitution, as well as many of the institutions provided the Criminal Code and legislation extravagant, here is that, because of the draconian laws and for some peculiar characteristics, the treatment of specialized courts when subjected to trial as it was the mansion of Military Justice Saturn